Landfill leachate treatment performance in subsurface flow constructed wetlands using safety flow system - Abdul Kadir, Aeslina (2004)
The increasing application of constructed wetlands for leachate treatment is an ever-growing incentive for the development of better process design tools. This study was conducted to investigate leachate treatment performance of horizontal subsurface flow constructed wetlands (HSSFCW) installed with water dispersal system, called Safety Flow® to produce a defined subsurface wetting pattern along the line and length of the system. A pilot scale HSSFCW with three parallel reactors was set up with dimensions of 2.45 m length x 0.20 m width x 0.40 m depth. All reactors were dosed using pre-treatment leachate effluent from sanitary landfill, lohor Bahru. Out of the three reactors, Reactors A and C were planted with I11yp/za angustifolia, whilst Reactor B was not planted and used as a control. In addition, Reactor C was installed with water dispersal system. The performance of constructed wetlands system was evaluated from the effluent quality. The main parameters were organics matter (biochemical oxygen demand (BOD) and chemical oxygen demand (COD), nutrients (ammonical nitrogen (NH4-N), nitrate (N03-N), phosphorus (P), and heavy metals (chromium (Cr) and cadmium (Cd). Based on the observation, Reactor C was found better than both Reactors A and B. Reactor C had removed more than 70% of BOD and COD, up to 80% of NH4-N and P and at least 90% of heavy metals.